The mace and the axe in the Iranian martial tradition, by Manouchehr Moshtagh Khorasani - Khorasani, Manouchehr Moshtagh (Revista de Artes Marciales Asiáticas, 2012)
The present article describes different types of maces and axes and their corresponding combat techniques based on Iranian martial arts tradition. Explaining different terms used by Persian manuscripts to refer to maces, the article then shows different types and expressions that talk about the weight and impact force of maces. Second, the article analyzes combat with maces: the way of carrying and drawing a mace, techniques of attack, offensive techniques against animals carrying the enemy, and defensive techniques. In the same manner, the article explains axes and their related techniques of attack. Some types of axes and maces as well as their techniques can be seen in pictures and miniatures in the article.